Towards the Altar: An In-depth Exploration of Seminarians’ Aspiration Towards Priestly Vocation - Mike Canoy; Ralph Kenneth Salinas; Efren Rey Genobesa; Jinggle Selgas (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
The seminary formation of Catholic aspirants to the priesthood is a complex journey that involves careful discernment of personal aspiration and motivation. Specific formation programs were designed and formulated to abet them in their vocation discernment. This study examines different motives that keep Propaedeutic seminarians in their initial formation phase. It is a case study investigating the other areas of seminary structure and personal motivation that impelled them to pursue seminary formation. The primary data for this study was obtained from the Holy Infant Seminary of the Diocese of Pagadian, a diocese in Zamboanga del Sur in the western hemisphere of Mindanao, Philippines. Employing the case study technique, the researchers conducted direct interviews with fourteen propaedeutic seminarians to evaluate and examine their motivation. The study's findings show three significant themes which help them cope with the demands of priestly formation: seminary activities or programs, strategies to nurture vocation, and personal motivation factors.